2022
DOI: 10.3390/su14116606
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Critical Success Factors for Enterprise Resource Planning Implementation Using Quantitative Methods in Agricultural Processing Companies

Abstract: This study aims to evaluate critical success factors (CSFs), considering the perspectives of various stakeholders who are involved in enterprise resource planning (ERP) implementation in agricultural processing companies in Central Macedonia (Greece). This evaluation—combined with aspects from the literature—may show how a digital production system can be managed and redesigned to become sustainable for a company. Research was conducted through the use of a specially designed questionnaire that was addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Descriptive statistics were used to present the results of the TAM scale responses. On the other hand, the Friedman test [40] was used to compare the results of each TAM scale question at the three survey times and Cronbach's alpha test [41] to determine the level of agreement between the experts and the reliability of the scale used. For all analyses, this work used a significance level of 0.05.…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…Descriptive statistics were used to present the results of the TAM scale responses. On the other hand, the Friedman test [40] was used to compare the results of each TAM scale question at the three survey times and Cronbach's alpha test [41] to determine the level of agreement between the experts and the reliability of the scale used. For all analyses, this work used a significance level of 0.05.…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…After examining the structural equation modeling, it is time to use the Friedman test to rank the research variables. In this section, the researcher intends to use the Friedman test to measure the importance of each variable from the respondents' point of view [49]. In fact, the Friedman test determines whether the sums of the ranks are significantly different from each other or not.…”
Section: Step 8: Friedman's Testmentioning
confidence: 99%
“…The critical success factor (CSF) of adopting new technologies is an exciting research topic that attracts many researchers, e.g., the success factors of business intelligence [5][6][7], enterprise resource planning [8,9], and artificial intelligence [10,11]. Regarding blockchain, Post et al identified the factors influencing blockchain-technology diffusion using grounded theory-based data collection and analysis [12].…”
Section: Related Workmentioning
confidence: 99%